The footprint of old syphilis: using a reverse screening algorithm for syphilis testing in a U.S. Geographic Information Systems-Based Community Outreach Program - Goswami, Neela D; Stout, Jason E; Miller, William C; Hecker, Emily J; Cox, Gary M; Norton, Brianna L; Sena, Arlene C (Sexually transmitted diseases, 2013)
The impact of syphilis reverse sequence screening has not been evaluated in community outreach. Using reverse sequence screening in neighborhoods identified with geographic information systems, we found that among 239 participants, 45 (19%) were seropositive. Of these, 3 (7%) had untreated syphilis, 33 (73%) had previously treated syphilis infection, and 9 (20%) had negative nontreponemal test results.